2022
DOI: 10.4103/jfmpc.jfmpc_770_21
|View full text |Cite
|
Sign up to set email alerts
|

Invasive fungal sinusitis-A neglected but important association with COVID 19 infection and a ticking bomb

Abstract: A retrospective analysis of severe acute respiratory syndrome (SARS) and influenza data worldwide has concluded that fungal coinfections associated with global SARS-coronavirus 2 (CoV-2) are likely to be missed or misdiagnosed. The coronavirus disease-2019 (COVID)-19 patients, especially those who are severely ill or immunocompromised, are more likely to suffer from invasive mycoses which require early detection and treatment. We report two such cases, one of which is a case of aspergillosis of unilateral orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…A research conducted by Peltola VT et al, using animal models has showed that H3N2 subtype gripal viruses are better partners of Streptococcus pneumonia in the induction of secondary bacterial infection such sinusitis [15]. The association between influenza, Covid-19 and invasive fungal sinusitis should not be neglected [16]. Cases of fulminant invasive fungal sinusitis after infection with SARS-CoV2 virus in the immunocompromised host have been reported [16,17].…”
Section: Sinusitismentioning
confidence: 99%
See 1 more Smart Citation
“…A research conducted by Peltola VT et al, using animal models has showed that H3N2 subtype gripal viruses are better partners of Streptococcus pneumonia in the induction of secondary bacterial infection such sinusitis [15]. The association between influenza, Covid-19 and invasive fungal sinusitis should not be neglected [16]. Cases of fulminant invasive fungal sinusitis after infection with SARS-CoV2 virus in the immunocompromised host have been reported [16,17].…”
Section: Sinusitismentioning
confidence: 99%
“…The association between influenza, Covid-19 and invasive fungal sinusitis should not be neglected [16]. Cases of fulminant invasive fungal sinusitis after infection with SARS-CoV2 virus in the immunocompromised host have been reported [16,17].…”
Section: Sinusitismentioning
confidence: 99%